Dynamic Characteristic Analysis and Experimental Investigation on Gearbox Housing of Heavy Scraper Conveyor - Cao Baolin; Zhang Yunbo; Lü Kaibo; Ji Chaoyue; Li Zhizhong; Lian Zisheng (Jixie chuandong)
The mechanical property of the gearbox directly affects the performance and life of the scraper conveyor controlled start transmission（ CST）. Under the rated load condition,through dynamics analysis simulation and experiments,the supporting dynamic reaction force and boundary condition of gearbox housing are determined,the transient stress and vibration response characteristics of the CST gearbox housing are analyzed,and the weak location of natural characteristic and rigidity of gearbox is acquired. The loading experiment of the CST gearbox is carried out,the surface stress and vibration signal and its spectrum of the housing are analyzed.The analysis shows that the stress of the housing surface is greatly lower than the allowable stress of the material of the housing,and the resonance of housing and gear transmission system could not happen. Also,the intermediate housing is considered as the weak stiffness part of the gearbox housing,and the housing vibration in the front of the output end is greater. The results could provide a theoretical basis and data support for the CST gearbox structure optimization design.